Asian popular culture - Fung, Anthony Y. H. (New York : Routledge, 2013)
"Examines two seemingly contradictory and yet parallel processes in the circulation of Asian popular culture: the interconnectedness between Asian popular culture and western culture in an era of cultural globalization, and the local derivatives and versions of global culture that are necessarily disconnected from their origins in order to cater for the local market"--Provided by publisher.
Introduction : Asian popular culture, the global (dis)continuity / Anthony Y.H. Fung -- One region, two modernities : Disneyland in Tokyo and Hong Kong / Micky Lee and Anthony Y.H. Fung -- Comic travels : Disney publishing in the People's Republic of China / Jennifer Altehenger -- When Chinese youth meet Harry Potter : translating consumption and middle class identification / John Nguyet Erni -- New forms of transborder visuality in urban China : saving face for magazine covers / Eric Kit-Wai Ma -- Cultural consumption and masculinity : a case study of GQ magazine covers in Taiwan / Hong-Chi Shiau -- An unlocalized and unglobalized subculture : English language independent music in Singapore / Kai Khiun Liew and Shzr Ee Tan -- The localized production of Jamaican music in Thailand / Viriya Sawangchot -- Consuming online games in Taiwan : global games and local market / Lai-Chi Chen -- The rise of the Korean cinema in inbound and outbound globalization / Shin Dong Kim -- Pocket capitalism and virtual intimacy : pokémon as a symptom of post-industrial youth culture / Anne Allison -- Playing the global game : Japan brand and globalization / Kukhee Choo -- China's new creative strategy : the utilization of cultural soft power and new markets / Michael Keane and Bonnie Liu -- Renationalizing Hong Kong cinema : the gathering force of the mainland market / Michael Curtin.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Popular culture -- Asia; Culture and globalization -- Asia; Mass media and culture -- Asia; East and West; Asia -- Civilization -- 21st century; Electronic books